Unraveling the impacts of progressive drought stress on the photosynthetic light reaction of tomato: assessed by chlorophyll-a fluorescence and gene expression analysis: Drought impacts on the photosynthesis in tomato - Nezamivand Chegini, Saber; Jafarinia, Mojtaba; Ghotbi-Ravandi, Ali Akbar (Cellular and Molecular Biology, 2024)
The present study aimed to investigate the impact of progressive drought stress (100%, 75%, 50%, and 25% of field capacity) on photosynthetic light reactions of tomato plants. The imposed drought caused a gradual reduction in leaf RWC leading to a decline in pigment concentration and growth indices. Significant alteration in the OJIP fluorescence transient curves and the formation of specific fluorescence bands (L, K, J, H, and G) gradually increased as drought severity increased. Phenomenological energy fluxes per excited cross-section (ABS/CS, TRo/CS, DIo/CS, ETo/CS and RC/CS) decreased with intensifying drought. As drought stress progressed, JIP-test parameters including The efficiencies of light reactions [φPo/(1- φPo )], the efficiencies of redox reactions [(ψo/(1-ψo)] and the efficiency of PSI to reduce the last electron acceptors [δRo/(1−δRo)] were significantly attenuated. The quantum yields for primary photochemistry (φPo), electron transfer from QA to QB (yO), electron transport (φEo), and reduction of end electron acceptors at the PSI acceptor side (φRo) were negatively affected by drought stress. These results indicate that drought progression leads to structural and functional damage in PSII, characterized by a decrease in active reaction centers, reduced energy absorption and trapping, diminished energetic connectivity within PSII, and inhibition of the oxygen-evolving complex. Additionally, reduced plastoquinone pool size, over-reduction of plastoquinone, and impaired redox state downstream of QB were observed at the donor side of PSII. The quantum yield and efficiency of PSI to reduce electron acceptors were reduced by drought progression. Our results showed that the transcript levels of PetE and PetF genes, encoding the key electron careers plastocyanin and ferredoxin, were significantly downregulated in response to an increase in drought severity, contributing to reduced PSI efficiency. The Transcript levels of PetE and PetF were reduced by 79% and 66% under 25% field capacity treatment, respectively. These results highlight critical points within the photosynthetic apparatus that are highly sensitive to drought, providing valuable insights into the mechanisms of drought-induced damage in tomato plants.